Detail of porte cochere om Mahapalika Marg - Ghosh, Ayan (2023)
Frederick W. Stevens designed the CSMT and BMC buildings within a decade of each other. As a result, both buildings have common features, design elements and building materials. Stevens described his building style as ‘...a free treatment of early Gothic with an Oriental feeling, which, I consider, the best adapted for the site the buildings are to occupy.’